2019
DOI: 10.3390/f10100848
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Sample Size on Parametrizing a Taper Curve Equation and the Resultant Stem-Volume Estimates

Abstract: Large and comprehensive datasets, traditionally based on destructive stem analysis or other labor-intensive approaches, are commonly considered as a necessity in developing stem-volume equations. The aim here was to investigate how a decreasing number of sample trees affects parametrizing an existing taper curve equation and resultant stem-volume estimates. Furthermore, the potential of terrestrial laser scanning (TLS) in producing taper curves was examined. A TLS-based taper curve was derived for 246 Scots pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This is also demonstrated by the fact that equation 7 has the minimum RMSE, MD, and MAD values. According to Maltamo et al (2019) and Saarinen et al (2019), the best model can be identified by its lowest RMSE. The findings of this study corroborate Islam & Ullah (2017) assertion that equation 7 is the optimal model for estimating volume based on tree diameter and height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also demonstrated by the fact that equation 7 has the minimum RMSE, MD, and MAD values. According to Maltamo et al (2019) and Saarinen et al (2019), the best model can be identified by its lowest RMSE. The findings of this study corroborate Islam & Ullah (2017) assertion that equation 7 is the optimal model for estimating volume based on tree diameter and height.…”
Section: Resultsmentioning
confidence: 99%
“…Selection of the best model is carried out by calculating the value of the coefficient of determination (R 2 ), coefficient of determination adjust (R 2 adj. ), t-test, root means square error (RMSE), mean deviation (MD), and mean absolute deviation (MAD) (Xia et al, 2013;Gonzalez-Benecke et al, 2014;Lee et al, 2017;Cañadas-López et al, 2019;Hernández et al, 2019;Maltamo et al, 2019;Saarinen et al, 2019;Brūmelis et al, 2020;Marzulli et al, 2020;Socha et al, 2020). This value is calculated as follows, using equations 10 to 15:…”
Section: Methodsmentioning
confidence: 99%
“…Data should be obtained from a carefully selected sample of trees that represents the variability of wood properties in the area (or population) of interest. For example, an analysis by Saarinen et al (2019) showed that a relatively small sample of representative individuals is enough to reparameterize an empirical stem taper function for a well-defined population.…”
Section: Applications In the Modeling Of Wood Properties And Wood Quamentioning
confidence: 99%
“…tree height, DBH, stem volume, crown-base height, height-diameter ratio, taper, lean, and sweep) of which most are attributes that have been generated also from traditional measurements. However, as shown by Jacobs et al (2019) and Saarinen et al (2019), taper curve is possible to obtain from TLS point clouds and it enables generation of unconventional attributes that may be used in revealing differences in the stem development and stem growth allocation.…”
Section: Introductionmentioning
confidence: 99%